1996
DOI: 10.1038/bjc.1996.608
|View full text |Cite
|
Sign up to set email alerts
|

What do cancer patients mean when they complain of concentration and memory problems?

Abstract: Summary Cognitive function items are increasingly included in quality of life measures, and complaints of concentration and memory difficulties are often reported by cancer patients. The aim of this study was to examine the factors influencing patients' level of complaint by comparing subjective reports with objective test performance of a sample of adult lymphoma patients, disease-free and > 6 months after treatment. There was no significant difference between complainers and non-complainers in sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
2
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(126 citation statements)
references
References 19 publications
9
111
2
4
Order By: Relevance
“…Obviously, the possibility of tumour recurrence presents a psychological burden with resultant anxiety, depression, or fatigue, which can negatively affect the patient's cognitive function. 17 The long-term cognitive impairment in patients with low-grade gliomas is similar to that seen in patients with mild-to-moderate traumatic brain injury. 31 When cognitive function is compromised because of the tumour or treatment, physical, social, and attitudinal factors will affect the patient's ability to compensate for these cognitive limitations.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Obviously, the possibility of tumour recurrence presents a psychological burden with resultant anxiety, depression, or fatigue, which can negatively affect the patient's cognitive function. 17 The long-term cognitive impairment in patients with low-grade gliomas is similar to that seen in patients with mild-to-moderate traumatic brain injury. 31 When cognitive function is compromised because of the tumour or treatment, physical, social, and attitudinal factors will affect the patient's ability to compensate for these cognitive limitations.…”
Section: Discussionmentioning
confidence: 88%
“…29 We saw a somewhat stronger relation between objective test results and self-reported cognitive function than that noted in earlier studies of patients with brain tumours and those with systemic cancer. 25,30 Cull and colleagues 17 suggested that cognitive complaints of cancer patients might actually indicate feelings of anxiety, depression, or fatigue. Moreover, a dissociation between objective cognitive test results and self-reported cognitive function holds true especially for patients with brain cancer whose judgment could be severely impaired by the tumour.…”
Section: Patient Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue that is commonly encountered in many studies of cognitive functioning in chronically ill patients is the discrepancy observed between the subjective (self-report) and objective (neuropsychological testing) measures of cognitive functioning [75][76][77][78][79][80][81]. The results of our trial suggest that this disconnect between subjective experience and test-based indicators of cognitive functioning not only applies in cross-sectional assessments, but also in assessing change in cognitive functioning over time.…”
Section: Expert Commentarymentioning
confidence: 78%
“…It has been proposed that objective test results and subjective reports of patients regarding their cognitive functioning and mood are not always related; there has been no relationship between the self-reported difficulties and the performance of patients in objective tests (Cull et al, 1966;Ly et al, 2001). Furthermore, PC patients with nonlocal cancer randomised either to AD or follow-up did not differ in subjective cognitive function (Green et al, 2002a,b).…”
Section: Cognition In Prostate Cancermentioning
confidence: 99%